Adaptations of cocoa and coffee farmers communities in the heart of remnant pristine forest of east Cameroon to institutional changes - Sonwa, D.J.; Weise, Stephan F.; Adesina, A.A.; Tchatat, M.; Ndoye, O.; Endamana, D. (2006)
With support provided by the state, cocoa and coffee are among the main perennial crops providing income to farmers living in the heart of the pristine forest of East Cameroon (Northern part of the Congo Basin). Regular in comes from these perennial crops have enabled farmers not to depend solely on forest resources. But During the 80s and 90s, some mains changes (cocoa and coffee crisis, liberalization of the economy and agricultural sectors and devaluation of local currency) occurred and influenced the management of cocoa and coffee. Based on participatory rural appraisal with 27 communities in the East province of Cameroon, the study evaluated (1)The dynamics of farmers’ practices before/during the crisis and the devaluation of local currency, (2)The comparison of income between perennial crops and other phytogenetic resources, (3)The current constraints on cocoa production and (4)Phytogenetic resource preferences of farmers in view of diversifying and increasing their income in and outside cocoa and coffee agroforest.